On periodic Gibbs measures of p-adic Potts model on a Cayley Tree - Mukhamedov, Farrukh; Khakimov, Otabek (Pleiades Publishing, Ltd, 2016)
In the present paper, we study the existence of periodic p-adic quasi Gibbs measures of p-adic Potts model over the Cayley tree of order two.We first prove that the renormalized dynamical system associated with the model is conjugate to the symbolic shift. As a consequence of this result we obtain the existence of countably many periodic p-adic Gibbs measures for the model.